PENINGKATAN HASIL BELAJAR GERAK DASAR TOLAK PELURU GAYA ORTODOKS MELALUI PENDEKATAN BERMAIN â€œRISHOâ€ PADA SISWA KELAS IV SDN JRAGUNG 2 KECAMATAN KARANGAWEN KABUPATEN DEMAK TAHUN PELAJARAN 2012 / 2013 (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2014)
The purpose of this study was to improve the learning outcomes of basic motion through the shot-put styleunorthodox approach to playing "risho". This research is a classroom action research (CAR), using the methodof data collection methods and non-test test (observation and documentation). Research subjects in this studywere fourth grade students of SDN Academic Year Jragung 2 2012/2013, amounting to 28 students.Classroom action research was conducted in two cycles. Research activities in each cycle includes planning,implementation, observation, and reflection. The results of this study showed the percentage of students in thelearning activities of the first cycle with both categories (93%) and the second cycle increased with very goodcategory (96%). The average grade achieved in the first cycle is 74.75 with classical completeness achievementthat is equal to 75% and the second cycle class average increased to 80.50 and the achievement of the classicalcompleteness of 96%. From the results of this study concluded that learning basic movement through the shotputstyle unorthodox approach to the game "risho" to improve student learning outcomes and studentactivities..